FORMATION OF THE SYSTEM OF BIOGEOCHEMICAL CYCLES - Zavarzin G.A. (My University, 2003)
Discoveries made during the past several decades in the field that may be defined as bacterial paleontology in the broad sense have given rise to modern views on the evolution of the geosphere-biosphere system. This has laid the basis for a new theory attaching great importance to cooperative interaction within the large system. The system in question goes beyond the population limits that are traditional for biologists and constitute the basis of Darwinism. Therefore, the realm of geosphere-biosphere systems may be called extra-Darwinian. In these systems, along with the determining influence of the geosphere on the biota, transforming feedback connections play an important part. The prokaryotic community, which catalyzes the system of biogeochemical cycles, serves as a basis of subsequent evolution. The increasing complexity of living organisms does not undermine the crucial importance of "the invisible" for the existence of the biosphere. Instead, it is superposed on the system that they have created. On the given scale, evolution is clearly additive.